Refractive Errors in Students Islamic Boarding School Islamic Association 31 Banjaran Bandung - Pamungkas, Motris; Adi, Mateus Sakundarno; Sutiningsih, Dwi; Kartasurya, Martha Irene; Budijitno, Selamat (Jurnal Epidemiologi Kesehatan Komunitas, 2025)
Background: Refractive errors are one of the most common causes of visual impairment, covering all age groups including children. The purpose of this study was to determine the description of refractive errors and demographic characteristics that occur in students at the Islamic Boarding School Persatuan Islam 31 Banjaran, Bandung Regency.Methods: This study used a cross-sectional study conducted from January to February 2024 at Pondok Pesantren Persatuan Islam 31 Banjaran, Bandung Regency. The sample was selected by total sampling. Subjects were examined using optotype snellen chart, students with visual acuity worse than 6/9 underwent further examination using refractometry, and correction using trial set lenses.Result: The results showed that of the total 674 students who took part in the visual acuity examination, 173 students (25.67%) had visual impairment with refractive errors. Refractive errors were more common among female students (69.79%) than male students (31.21%). Refractive errors were more common in 14-15 year olds (21.38%) compared to other age groups. The most common types of refractive errors were myopia (45.67%), astigmatism (36.99%), myopic astigmatism (15.03%), and hyperopia (1.73%). In addition, there were also students suspected to have organic disorders (0.5%) who experienced lazy eye (amblyopia).Conclusion : Early detection efforts of visual impairment need to be carried out by parents, school teachers, health workers and the government by conducting regular visual acuity screening and refractive error examinations at all levels of society, especially school-age children